SPECIFIC ASPECTS OF THE RECOGNITION OF LIABILITIES - Jabbarova Charos Aminovna (American Journals, 2024)
This article dedicates to research the recognition and valuation of liabilities including the recognition, valuation and reflection of assessed liabilities in accounting and conclusions are formulated based on the results of the study.
Keywords: Liabilities, long-term and current liabilities, explicit liabilities, indefinite liabilities, estimated liabilities, conditional liabilities.